Evaluasi Anggaran Terhadap Akuntabilitas Pada Kantor Wali Kota Medan - Syah, Arieffan; Daulay, Aldi Raihan Ramadhan; Zaman, Muhammad Qomaruz (LPPM Universitas Labuhanbatu, 2023)
By comparing the budget with the realization and using it as a basis for determining accountability, budget evaluation is a process used to track deviations from the budget plan. The Medan Mayor's office has an accountability problem that hinders its effectiveness: it does not issue financial reports or income and expenditure realization reports. Given the issues raised in this research, the aim of this research is to ascertain how budget evaluation affects accountability. The 32 respondents who work in the Medan mayor's office were given a questionnaire as part of the method used in this study. The research results show that accountability is influenced by budget evaluation, and the impact is very positive.